Strategi Kepolisian Polda Bengkulu dalam Pencegahan Mafia Tanah Perspektif Fiqih Siyasah - Agus Kesuma; Rohmadi; Toha Andiko (CV. Doki Course and Training, 2024)
The purpose of this study was to determine the strategy of the Police in the Directorate of General Criminal Investigation of the Bengkulu Regional Police in preventing and prosecuting land mafia figures in Bengkulu City and how the perspective of Fiqh Siyasah on the strategy of the Police in the Directorate of General Criminal Investigation of the Bengkulu Regional Police in preventing and prosecuting land mafia figures in Bengkulu City. The type of field research, namely the object of research directly at the Directorate of General Criminal Investigation of the Bengkulu Regional Police using a qualitative approach. The research methods used were observation, interviews and documentation. The results of the study showed that the Strategy implemented by the Bengkulu Regional Police, Directorate of General Criminal Investigation in preventing and prosecuting land mafia figures has succeeded in reducing and narrowing the room for movement for land mafia figures and also the police's efforts to increase public insight have helped the public avoid the enticements and modes used by land mafia figures. Then by forming a Land Mafia Task Force consisting of the National Land Agency (BPN), the High Prosecutor's Office and the Police, it has succeeded in creating good collaboration between agencies so that there is a reduction in land mafia cases in the city of Bengkulu. Meanwhile, according to Islamic jurisprudence, land mafia or land fraud is strictly prohibited, individuals who commit fraud are classified as people who are unjust, the police strategy that has been carried out is in accordance with the principles of the court (al-qadha) and peace (ishlah). Thus, the settlement of disputes carried out by the Bengkulu Regional Police is in accordance with Islamic Law.